Analisis Hukum terhadap Penyalahgunaan Narkoba di Kalangan Remaja dan Upaya Penanggulangannya, Studi Kasus Polres Binjai: Legal Analysis of Drug Abuse Among Adolescents and Efforts to Overcome It: A Case Study of the Binjai Police - Putri Dwi Sari; Rica Gusmarani (Jurnal Hukum Bisnis, 2026)
Drug abuse among adolescents has become a serious problem in Indonesia, not only impacting physical and mental health but also having broad legal and social implications. This phenomenon raises concerns for the public, the government, and law enforcement officials, as adolescents, as the nation's future generation, should be free from destructive behavior that can damage their future and disrupt social stability. This study uses a normative juridical research method that focuses on examining legal regulations in legislation related to drug abuse. The approaches used include a statute approach and a case approach, examining various laws, regulations, and cases related to this legal issue. The data sources used are secondary data obtained through literature studies, which were then analyzed using qualitative analysis methods. The results of the study indicate that drug abuse among adolescents occurs due to a complex interaction of internal and external factors. Internal factors include unstable psychological conditions, impulsivity, emotional stress, and the search for self-identity, which makes adolescents vulnerable to trying addictive substances as a form of escape from problems. Meanwhile, external factors stem from the social environment, lack of family supervision, and negative social influences. Therefore, an integrated and collaborative approach between families, communities, educational institutions, and law enforcement is needed to create an effective strategy to suppress drug abuse in the Binjai Police jurisdiction.